THE ROLE OF INSTAGRAM MARKETING AND BRAND AWARENESS IN DRIVING PURCHASE DECISIONS OF SEAFOOD AT FOREMORE RESTO & CAFE, SURABAYA: THE MEDIATING EFFECT OF PURCHASE INTENTION - Abidin, Zainal; Hamonangan , Yeremia Neuville (Universitas Mataram, 2025)
Social media marketing strategies have become a solution to enhance business competitiveness, particularly for entrepreneurs in the fisheries sector. However, intense competition and low brand awareness of new seafood menu offerings pose challenges for Foremore Resto & Cafe. This study aims to analyze the influence of social media marketing, brand awareness, and purchase intention on purchasing decisions for seafood products at Foremore Resto & Cafe. Data on consumer behavior were collected from 143 respondents using a questionnaire. The data analysis techniques employed include Structural Equation Modeling Partial Least Squares (SEM-PLS) using WarpPLS version 8.0 and quantitative descriptive analysis. The findings indicate that social media marketing and brand awareness play a crucial role in increasing consumers' purchase intention toward seafood products at Foremore Resto & Cafe. Brand awareness directly contributes to enhancing purchasing decisions, whereas social media marketing does not show a direct influence on purchasing decisions. Thus, optimizing social media marketing and brand awareness are key factors in fostering an effective purchase intention that leads to increased purchasing decisions for seafood products at Foremore Resto & Cafe.